The “Heart Pedagogy” of St. Augustine - Dzenuškaitė, Stasė (Acta Paedagogica Vilnensia, 2005)
The article represents the "Pedagogy of the Heart" as an essential point of the writings of the outstanding teacher of the Christian Church of the Patristic period. The article surveys briefly the pedagogical activity of St. Augustine and emphasizes the main principles of his pedagogical attitudes, also it focuses on the importance of nurturing the human heart at our times. By characterizing St. Augustine as an educator the paper also reveals the sources and main principles of his teaching. Grounding on works of St. Augustine and writings of other researches of his heritage allows to state, that all of his work were written "by heart" for "hearts". That’s why they all lift a heart of the reader God. Transformation of the heart of every human is an important concern of the pedagogy and among all the means leading to it the silent prayer must be mentioned as the one which helps human heart to come closer to the eternal religious sources.